Violaxanthin inhibits nonphotochemical quenching in light-harvesting antenna of Chromera velia - Kaňa, Radek; Kotabová, Eva; Kopečná, Jana; Trsková, Eliška; Belgio, Erica; Sobotka, Roman; Ruban, Alexander V (FEBS letters, 2016)
Non-photochemical quenching (NPQ) is a photoprotective mechanism in light-harvesting antennae. NPQ is triggered by chloroplast thylakoid lumen acidification and is accompanied by violaxanthin de-epoxidation to zeaxanthin, which further stimulates NPQ. In the present study, we show that violaxanthin can act in the opposite direction to zeaxanthin because an increase in the concentration of violaxanthin reduced NPQ in the light-harvesting antennae of Chromera velia. The correlation overlapped with a similar relationship between violaxanthin and NPQ as observed in isolated higher plant light-harvesting complex II. The data suggest that violaxanthin in C. velia can act as an inhibitor of NPQ, indicating that violaxanthin has to be removed from the vicinity of the protein to reach maximal NPQ.
Keywords: Photochemical Processes; fluorescence; chlorofyl; xanthofyly; Time Factors; časové faktory; Alveolata; Fluorescence; světlosběrné proteinové komplexy; Chlorophyll; Xanthophylls; fotochemické procesy; Light-Harvesting Protein Complexes